Les dynamiques contradictoires du champ associatif syrien - Mathieu Le Saux (Université de Provence, 2006)
In spite of the authoritarian presence of the state under Bachar Al-Assad, new associations have emerged in recent years and benefited from a reformist Zeitgeist centered on the theme of "good government". Promoted to the rank of partner, "civil society" saw the emergence of non-governmental organizations (NGO) on a national scale, supporting the renewal of the non-profit, associative sector whose very existence implies a skirting of legal provisions and government controls. A new field thus appears where room for maneuver is conditional upon incessant negotiations between civil society and the regime. The latter continues to impose its methods insofar as it determines the relations these associations have between them, thus condemning the sector to obvious atomization and marginality.